#Tech4Bad: when do we say no?. (11th January 2022) - Brooks, Ian; Thorslund, Minna Laurell; Biørn-Hansen, Aksel; Somova, Elena
Abstract: Existing IT systems are enabling company activities that are unsustainable and damaging to the environment. 'When should we as IT professionals stop maintaining them?' ask Ian Brooks MBCS, Minna Laurell Thorslund, Aksel Biørn-Hansen and Elena Somova.